Efetividade da auriculoterapia na dor de pessoas portadoras de câncer em tratamento quimioterápico: um ensaio clínico randomizado - Ruela, Ludmila De Oliveira (2017)
Pain is a symptom feared by all people and, when a patient with a diagnosis of cancer suffers a worsening in this illness, there is a 90% estimation of having this symptom. The efforts to control it adequately have been many, yet cancer pain numbers continue to grow. In this context, the use of complementary therapies for pain management, rather than conventional ones, has been increasingly used by these patients. One of the most commonly used methods is acupuncture, including auricular therapy. This technique, which can be applied by a nurse, seeks to reestablish the balance of the body through stimuli at specific points of the auricular pavilion, with the aim of either preventing or curing an illness. Therefore, this study aimed to evaluate the effectiveness of auricular therapy in treating the pain of cancer patients undergoing chemotherapy. It is a randomized, controlled, masked clinical trial. The sample consisted of 23 cancer patients under chemotherapy treatment, accompanied by the High Complexity Assistance Unit of a municipality in the Southwest of Minas Gerais. To obtain the results, two parallel groups were formed by means of the stratified randomization: Treated group (n = 11), which received eight auricular therapy sessions at the Shenmen points - Kidney, Sympathetic, Muscular Relaxation and Individual Pentagram points, as well as Placebo Group (n = 12), in which the participants received eight auricular therapy sessions in two fixed placebo points, eye, and trachea. A blinded evaluator evaluated the participants, using the Numerical Pain Scale, the McGill Pain Questionnaire, and instruments developed by the researchers. After the intervention, there was a significant difference (P <0,05) between the two groups in pain intensity and classification, the qualitative descriptors of pain (sensory and total), the number of pain sites and the consumption of analgesics. Moreover, the Treated Group showed better results over time compared to the Placebo Group. Thus, we observed that auricular therapy was an effective technique in the reduction of cancer pain. In this context, it is recommended to use this technique in the control and relief of cancer pain, as a complementary treatment to the conventional ones and the implementation of this method in the health services for the care of cancer patients. It is hoped that this study will contribute to the encouragement of health professionals, especially nurses, seeking auricular therapy as a complementary method in pain relief during planning and in actions directed to cancer patients. However, new studies with methodological rigor should be developed to strengthen the scientific evidence about the use of auricular therapy for the pain management of cancer patients and, consequently, to provide better quality of life and improve the acceptance of this technique by professionals while planning their care.